Bejaka ditt husdjur och bejaka djuret inom dig! - AnnCristin Winroth (Kulturella Perspektiv, 2011)
This article presents, analyse and challenge the issue of nature and culture, animal and human, and arguments for a need for sharpening the “etnographic gaze” for the meaning of and exchange between animalish, human and the mixture of them both, in current representations in popular culture.